2015
DOI: 10.3389/fpls.2015.00092
|View full text |Cite
|
Sign up to set email alerts
|

Differential response to sulfur nutrition of two common bean genotypes differing in storage protein composition

Abstract: It has been hypothesized that the relatively low concentration of sulfur amino acids in legume seeds might be an ecological adaptation to nutrient poor, marginal soils. SARC1 and SMARC1N-PN1 are genetically related lines of common bean (dry bean, Phaseolus vulgaris) differing in seed storage protein composition. In SMARC1N-PN1, the lack of phaseolin and major lectins is compensated by increased levels of sulfur-rich proteins, resulting in an enhanced concentration of cysteine and methionine, mostly at the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 75 publications
(91 reference statements)
2
26
0
Order By: Relevance
“…In light of the scientific literature, the effect of S fertilization may also depend on the genotype, i.e. variety [63]. Our results, however, are in line with Mona et al [21], who proved that K fertilization causes slim increase in Lys and Cys in faba bean seeds.…”
Section: Discussionsupporting
confidence: 90%
“…In light of the scientific literature, the effect of S fertilization may also depend on the genotype, i.e. variety [63]. Our results, however, are in line with Mona et al [21], who proved that K fertilization causes slim increase in Lys and Cys in faba bean seeds.…”
Section: Discussionsupporting
confidence: 90%
“…e subject of the study was the cultivar Aura of common bean (Phaseolus vulgaris L.). e scheme of the study included the following treatments: O-control (without sulphur and molybdenum), Momolybdenum (100 g•ha − 3 •ha −1 (chizalofop-P-etylu 50 g•ha −1 ) were applied after emergence, when the first pair of trifoliate leaves had unfolded in beans plants (BBCH [13][14]. Beans were grown on-site, where the previous crop was spring barley.…”
Section: Methodsmentioning
confidence: 99%
“…Leguminous crops are unique in the high protein content of their seeds and their ability to fix atmospheric nitrogen [1]. Legume seeds are also very good sources of proteins and amino acids in human and animal nutrition [2,3]. According to Sulieman et al [4], plants that acquire N by biological fixation (BNF) have a higher sulphur (S) requirement than those which use only soil N. In the physiology of legumes, sulphur has a dual role: it is necessary, as a component of methionine, cystine, and cysteine, for the biosynthesis of proteins and for the biological reduction of molecular nitrogen [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…those that cannot be synthesised by the body and therefore must be obtained by the diet) in significant quantity [54]. Genetic and agronomic factors may influence the amino acid profile of cowpea [55]. Analyses carried out by Frota et al [56] and Vasconcelos et al [57] have shown that cowpea presented cysteine and methionine as limiting amino acids, whereas the other essential amino acids met the recommendations of the amino acid standard of the FAO/WHO [58] for children (2-5 years).…”
Section: Proteinmentioning
confidence: 99%